How does implementation of the Nagoya Protocol on Access and Benefit-Sharing affect biodiversity research? - Zonneveld, M. van; Loo, J.; Maselli, S.; Madrid, J.J.; Halewood, Michael; Echeverría, J.L. (2016)
In 2014 the Nagoya Protocol on Access and Benefit-sharing took effect and is being implemented by countries. This is important for fair and equitable sharing of benefits derived from genetic resources. However, scientists are concerned about its effect on non-commercial research, which has scientific, societal and environmental benefits beyond commercial gains. Such research may be delayed by cumbersome procedures and hampered by poor understanding of its scientific purposes and research requirements. Such delays negatively affect both biodiversity conservation and sustainable development. A test case in Guatemala revealed how the Nagoya protocol functions in practice for non-commercial genetic research. We piloted the steps required for the national authority to approve a request for genetic material to be extracted and shipped out of the country for analysis as part of a research project on conservation genetics. We draw lessons for improving the Nagoya process in subsequent cases. This study focused on understanding the impact of timber harvesting on the regeneration of the most valuable timber species, mahogany, in community-managed forests in the Maya Biosphere Reserve. Our request to collect and analyse seeds and leaves was approved after 1.5 years. As this was the first study to be reviewed considering the Protocol in Guatemala, there were no standard criteria or procedures. This pilot provided valuable lessons to the national authority for standardising and shortening procedures. These procedures should be based on national regulations, which are currently under development. Good communication by scientists is vital because many people may not understand what genetics studies mean nor realise their potential benefits for communities and society. In our case, the forest communities, who were consulted at the start, supported the study after they understood that this investigation is seeking evidence of their sustainable management. When implementing Nagoya, we encourage governments to establish committees including scientists, community representatives and other stakeholders to advise them. This helps to build trust among actors and ensure that different viewpoints are reflected in the codes of conduct. We encourage scientists to reach out to non-scientists to demonstrate to governments, local communities and society the relevance of their research.